Feed supplementation with potentiated zinc and/or tannin-rich extracts reduces ETEC infection severity and antimicrobial resistance genes in pig - Ollagnier, Catherine; Mellino, Maria-Rita; Pradervand, Nicolas; Tretola, Marco; Dubois, Sebastien; Durosoy, Stephane; Desrues, Olivier; Bellon, Johana (Frontiers in Veterinary Science, 2025)
Most antimicrobials used in pig production are prescribed to treat post-weaning diarrhea (PWD), which constitutes a major health issue in pig production. With the spread of multidrug-resistant pathogens, finding solutions to diminish the severity of PWD without antibiotics has become increasingly critical. Potentiated forms of zinc oxide (ZnO) and plant-based bioactive compounds like tannins have been shown to alleviate the severity of diarrhea, thus reducing the need for antibiotic treatment. The aim of this project was to test whether a potentiated form of ZnO (pZnO), alone (study 1) or in combination with tannin-rich extract (study 2), can be used in starter diets for weaned piglets infected by enterotoxigenic Escherichia coli (ETEC) to reduce PWD severity. At 26 ± 1.6 days of age (average body weight 7.8 ± 1.02 kg), 160 piglets (study 1, n = 72; study 2, n = 88) were randomly and equally assigned to four dietary treatments (study 1 = 18; study 2 = 22 pigs/group) and orally infected 4 days after weaning with a solution containing 1010 ETEC F4. Study 1 compared the effect of 150 mg Zn/kg pZnO (pZnO-150) and 300 mg Zn/kg pZnO (pZnO-300) to a negative control (C) and a positive control, 3,000 mg Zn/kg ZnO (C-3000). In study 2, a combination of 7.5 g/kg tannin extract (quebracho and chestnut) and 150 mg Zn/kg pZnO (TAN+pZnO-150) was compared to pZnO-150 and 7.5 g/kg tannin-rich extract (TAN) alone and to a negative control (C). The fecal score, bodyweight, daily food intake per pen, fecal F4 ETEC and Zn levels were analyzed. The small intestine content was sampled 9 days after infection to analyze the number of antimicrobial resistance genes. Regardless of the inclusion level, TAN+pZnO-150, TAN and pZnO led to a reduction in antibiotic treatment (p < 0.05), but only TAN and TAN+pZnO-150 reduced the fecal score (p < 0.05). C-3000 improved the average daily gain (p < 0.05). Tannin-rich extract and potentiated zinc oxide (pZnO) in starter diets effectively reduce the need for antibiotics in ETEC-challenged piglets. Traditional high-dose ZnO improved growth rates, but lower-dose alternatives with tannins provided health benefits without high zinc levels. These findings highlight sustainable dietary strategies to manage post-weaning diarrhea, supporting reduced antibiotic use in pig production.